Biofilm formation of hypermucoviscous and non-hypermucoviscous Klebsiella pneumoniae recovered from clinically affected African green monkey (Chlorocebus aethiops sabaeus). (June 2017) - Soto, Esteban; Dennis, Michelle M.; Beierschmitt, Amy; Francis, Stewart; Sithole, Fortune; Halliday-Simmons, Iona; Palmour, Roberta
Abstract: In recent years, an emergent Klebsiella pneumoniae hypermucoviscous (HMV) phenotype has been associated with increased invasiveness and pathogenicity in primates. The HMV phenotype is characterized by different capsular serotypes, associated with several genes including the rmpA (regulator of mucoid phenotype) and magA (mucoviscosity-associated) genes. In African green monkeys (AGM) ( Chlorocebus aethiops sabaeus ) serotypes K1 and K5 have been implicated in fatal multisystemic abscesses. In order to better understand the epizootiology of this pathogen, the capacity of biofilm production of K. pneumoniae isolates presenting the HMV was compared to non-HMV isolates at three different temperatures (25, 30 and 37 °C). The results indicate that HMV and non-HMV isolates display similar capacity to form biofilms at the three different evaluated temperatures. Temperature appears to play a role in the formation of biofilms by K. pneumoniae presenting the HMV phenotype, where larger biofilms were formed at 37 °C than at 25 °C. Knowledge regarding local environmental sources of K. pneumoniae and the possible role of wildlife in the maintenance of this agent in the area is necessary to develop effective recommendations for the prevention and management of this disease in captive AGM populations. Highlights: Biofilm formation of hypermucoviscous and non-hypermucoviscous Klebsiella pneumoniae serotypes are compared. Biofilm formation of Klebsiella pneumoniae at 25, 30 and 37 °C are compared. In vivo biofilm formation of Klebsiella pneumoniae in African green monkeys is proposed.